An investigation of the factors that influence participation in mammography screening in Greece - Kaltsa, Aikaterina (2011)
This thesis examines and explores women's mammography screening experiences and the factors influencing women's screening behaviours and choices. The sample consisted of Greek women who were recruited from women's organizations in Athens. 189 women completed a survey questionnaire about their values and beliefs in relation to mammography screening, 33 of whom subsequently underwent an in-depth interview to explore their experiences of mammography screening and their decision-making processes. According to the findings, women's mammography screening behaviour depended to a great extent on the quality and nature of their interactions within their social networks. Thus, the quality of information and meanings derived from these interactions was what determined women's behaviour. Family, close friends and doctors appeared to be important in the formation of women's beliefs, perceptions, emotions (fear of cancer) and behaviour in relation to breast screening. Interestingly, fear of cancer had an opposing effect towards their screening behaviour. A tentative model is presented, which attempts to explain the way these influences affect beliefs, perceptions and mammography screening behaviour, using elements of existing behavioural models. Further exploration of the influential factors and associations identified in this study is required.